The Influence of Principal's Leadership Style and Work Motivation on Teacher Performance - Zebua, Syukurman; Haluk, Paskalis; Pinoa, Stevan Andy; Kahfi, Al; Dzulhasnan, Ainul Haninah (Thawalib: Jurnal Kependidikan Islam, 2025)
Teacher performance is influenced by leadership, motivation, and other factors that affect the quality of learning, student achievement, and teachers' professional development. This study aims to explain the influence of leadership and motivation on teacher performance and their combined impact at SMP Taruna Harapan Bangsa Cigelam. The research employed a quantitative correlational method, with data collected using a questionnaire based on a Likert scale. Data were processed using validity and reliability tests, classical assumption tests, and both t-test and F-test analyses. The results showed that the principal's leadership style and work motivation significantly influenced teacher performance. The significance values for each variable were below 0.05, with positive Beta values (0.507 and 0.453), indicating a positive relationship. The overall regression model was significant, and the R Square value of 0.660 indicated that the two variables contributed 66% to teacher performance. Conclusion: An effective leadership style and high work motivation significantly improve teacher performance, although the incentive system indicator did not show a significant effect.